2018
DOI: 10.28945/4106
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Adoption of Social Media: An Integrated Model and Empirical Study on Facebook Usage

Abstract: Aim/Purpose: This study aims at (1) extending an existing theoretical framework to gain a deeper understanding of the technology acceptance process, notably of the Facebook social network in an unexplored Middle East context, (2) investigating the influence of social support theory on Facebook adoption outside the work context, (3) validating the effectiveness of the proposed research model for enhancing Facebook adoption, and (4) determining the effect of individual differences (gender, age, experience, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
(99 reference statements)
4
12
0
1
Order By: Relevance
“…Al-Azawei (2018) showed that perceived pleasure could reduce cognitive burden, thus removing the barriers to using an SNS. Consequently, individuals could continue using the technology, as the present-day depiction of SNS allows users to deploy less effort and feel greater enjoyment (Al-Azawei, 2018). Various multimedia resources and features of an SNS make it an outlet for excitement and respite (Al-Azawei, 2018).…”
Section: Research Model and Hypothesis Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Azawei (2018) showed that perceived pleasure could reduce cognitive burden, thus removing the barriers to using an SNS. Consequently, individuals could continue using the technology, as the present-day depiction of SNS allows users to deploy less effort and feel greater enjoyment (Al-Azawei, 2018). Various multimedia resources and features of an SNS make it an outlet for excitement and respite (Al-Azawei, 2018).…”
Section: Research Model and Hypothesis Statementsmentioning
confidence: 99%
“…Consequently, individuals could continue using the technology, as the present-day depiction of SNS allows users to deploy less effort and feel greater enjoyment (Al-Azawei, 2018). Various multimedia resources and features of an SNS make it an outlet for excitement and respite (Al-Azawei, 2018). Casaló et al (2017) confirmed perceived pleasure as a key aspect for stimulating a satisfaction-intention-behavior chain that increases users’ interactions with social media.…”
Section: Research Model and Hypothesis Statementsmentioning
confidence: 99%
“…According to Watat, Fosso Wamba, and Kala Kamdjougs (2018), most users of SNS are the youth attending various educational institutions at different academic levels. In contrast, these social-networking sites have been recently introduced into certain developing countries like Iraq, which have previously prohibited Internet use for many years (Al-Azawei et al, 2016b;Al-Azawei, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for these differences can be related to the education level of the respondents. It is because of the existence of a positive relationship between education level and doing online marketing activities (Al-Azawei, 2018;Deryabina & Trubnikova, 2020). According to research data, the respondents in Slovakian and Hungarian microenterprises (76.02% and 83.2%) and older Slovakian and Hungarian SMEs (76.85% and 81.35%) are more educated than their Czech counterparts, since the percentages for highly educated Slovakian and Hungarian owners and managers are higher than the respondents from Czech microenterprises and older SMEs (46.21% and 51.34%).…”
Section: Discussionmentioning
confidence: 99%